Planar graphene multifunctional component. Issue 7 (July 2015) - Dmitriev, Victor; Nascimento, Clerisson
ABSTRACT We suggest and investigate theoretically a new graphene electromagnetic tunable multifunctional component for THz region. The structure represents a planar square array of graphene elements placed on both sides of a thin dielectric substrate. By changing electrostatically the graphene chemical potential, the frequency characteristics of the pass‐band and stop‐band filter can be displaced providing a dynamic control of the filter. This property and combination of a high peak and a deep valley in the transmission response allow one to use the component also as a switch in two different frequency controllable bands. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1755–1760, 2015